Model UTAUT untuk Menjelajahi Faktor-faktor yang Mempengaruhi Adopsi QRIS di Malang - Muhammad Aunul Mubarok; Devina Tsabitah; Laras Ayu Ningtias; Kurniawati Meylianingrum; Ayub Wijayati Sapta Pradana (Pustaka Peradaban, 2023)
In this quantitative descriptive research study, we investigate the adoption of the Indonesian Standard Quick Response Code (QRIS) among economics students in the Malang region. Our particular focus centers on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The research involves a sample of 120 economics students drawn from UIN Malang, Univ Brawijaya, and Univ Negeri Malang. Data collection is conducted through a questionnaire that examines four key variables: performance expectancy, effort expectancy, social influence, and facilitating conditions. The findings underscore the significant influence of performance expectancy on the intention to use QRIS, while the remaining variables exhibit positive yet non-significant relationships. This study provides valuable insights into the pivotal role of performance expectancy in driving QRIS adoption among economics students and highlights its potential implications for fostering a sustainable economy in the Malang region.